2011
DOI: 10.1007/s10286-011-0130-x
|View full text |Cite
|
Sign up to set email alerts
|

Fludrocortisone improves nausea in children with orthostatic intolerance (OI)

Abstract: Association of EGG abnormalities and OI in this subset of nausea patients suggests a generalized disturbance of autonomic regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…As we have previously reported (12,13), pediatric subjects presenting with various OI symptoms frequently demonstrated an abnormal HUT, raising the possibility of a cardiovascular basis for their OI, including gastrointestinal symptoms. The majority (62.5%) of patients with reported orthostatic dizziness were HUT(ϩ), consistent with findings in adults (36) patients experienced syncope later in the HUT (10).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As we have previously reported (12,13), pediatric subjects presenting with various OI symptoms frequently demonstrated an abnormal HUT, raising the possibility of a cardiovascular basis for their OI, including gastrointestinal symptoms. The majority (62.5%) of patients with reported orthostatic dizziness were HUT(ϩ), consistent with findings in adults (36) patients experienced syncope later in the HUT (10).…”
Section: Discussionmentioning
confidence: 71%
“…Increases in AVP and Epi during HUT have also been observed in both adult OH and vasovagal syncope subjects (23,32,37). OI is also observed in pediatric patients (12) but is particularly difficult to diagnose and treat as it is underrecognized, and testing, such as HUT, can be invasive for children. Characterization of the neurohumoral response to orthostatic challenge in children with OI has not been well described, but dysregulation of these systems likely plays a role in its pathogenesis (12,13).…”
mentioning
confidence: 99%
“…The possible causes of this were discussed earlier in this chapter. As described earlier, nausea replicated during HUT (therefore secondary to an orthostatic challenge) often improves with volume expansion with fludrocortisone (Fortunato et al, 2011;Sullivan et al, 2005).…”
Section: Migrainementioning
confidence: 61%
“…A few elegant studies have shown the relationship of the orthostatic challenge and gastrointestinal symptoms. The gastrointestinal symptoms that often occur during HUT include nausea and abdominal pain (Fortunato et al, 2011;Fortunato et al, 2014;Sullivan et al, 2005). Moak et al performed 24-h antroduodenal manometry studies in pediatric patients with OI and GI symptoms and tilted the subjects during the antroduodenal motility study.…”
mentioning
confidence: 99%
See 1 more Smart Citation